Investigation of the effect of boron carbide addition on semiconductor zinc oxide nanoparticles on their structural, morphological, and dielectrical properties - Macit, Cevher Kursat; Gurgenc, Ezgi; Biryan, Fatih; Ozen, Furkan; Gurgenc, Turan; Ozel, Cihan (Springer, 2023)
In the present study, pure zinc oxide (ZnO) and boron carbide (B4C) doped ZnO nanocomposite particles were fabricated by using the sol-gel method. The effect of B4C addition on ZnO nanoparticles on their structural, morphological, and dielectrical properties was investigated. The synthesized nanoparticles were characterized by using FE-SEM, XRD, EDX, and FT-IR analyses. The dielectrical behavior of nanoparticles was found by an impedance device. Pure ZnO and B4C-doped ZnO composite particles consist of nano-sized structures. In XRD analyses, no peaks belonging to secondary phases were detected and it was observed that pure and B4C-doped ZnO nanoparticles were successfully formed. It was determined that as the B4C doping increased, the intensities of the characteristic peaks of ZnO decreased, while the intensities of the characteristic peaks of B4C increased. ZnO are in an almost spherical-like form and are agglomerated. In the doped samples, ZnO nanoparticles are found locally agglomerated on the B4C nanoplates. It was observed that the B4C additive was effective on the dielectrical properties and improved the dielectrical properties. As the temperature increased, the AC and DC conductivities of all produced nanoparticles increased. Based on the results obtained in the study, it was thought that a competitor material to pure ZnO nanoparticles was synthesized in semiconductor devices and electronic devices and offers great potential for electronic device applications.
Keywords: Light-Harvesting Applications; Zno Nanoparticles; Optical-Properties; Calcination Temperature; Hydrothermal Synthesis; Thin-Film; Nanostructures; Behavior; Degradation; Nanosheets